2021
DOI: 10.1002/cbic.202000852
|View full text |Cite
|
Sign up to set email alerts
|

Fluorophosphonates on‐Demand: A General and Simplified Approach toward Fluorophosphonate Synthesis

Abstract: This article is part of a Special Collection on Chemical Translational Biology. Please see our homepage for more articles in the collection. Figure 1. Common uses and synthesis of activated phosphonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Recently, Dutra et al found a solution to the instability of FPprobes by using nitrophenyl phosphonates, which can be turned into fluorophosphonates on demand through reaction with a resin-supported fluoride source. [36] We think that this may be a useful future option for the here reported alkyne-and BODIPY-conjugated FP-probes.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Recently, Dutra et al found a solution to the instability of FPprobes by using nitrophenyl phosphonates, which can be turned into fluorophosphonates on demand through reaction with a resin-supported fluoride source. [36] We think that this may be a useful future option for the here reported alkyne-and BODIPY-conjugated FP-probes.…”
Section: Discussionmentioning
confidence: 92%
“…We did not choose this here, because a possible drawback is the formation of triphenylphosphine oxide, which we experienced in other reactions to be cumbersome to remove. Note that this concern is unnecessary, as FP‐probe synthesis using the Appel reaction has been reported by others without negative effect on the yield [23,36] . The route towards an FP‐alkyne probe may even be shortened by an additional step when using 6‐heptyn‐1‐ol, 9‐decyn‐1‐ol or 10‐undecyn‐1‐ol as starting material.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Dutra et al reported the development of activated phosphonate activity-based probes, including a pomalidomide-linked derivative, which might be useful for the profiling of CRBN binding partners. 157,158 In their studies, the fluorophosphonate warhead was directed against serine hydrolases. Its synthesis proceeded via a mixed aryloxyphosphonate intermediate 105 (Scheme 16) whose p-nitrophenol leaving group was exchanged by a polymer-supported fluoride reagent.…”
Section: Crbn-directed Molecular Gluesmentioning
confidence: 99%
“…A mixed phosphonates has been reported as a tunable warhead group for serine hydrolases (Table 1). 28 Mixed phosphonates with a p ‐nitrophenol leaving group in particular showed high reactivities with a variety of serine hydrolases and higher stability in storage when compared to FPs 29 . To facilitate understanding of the substrate‐enzyme interaction of NRPS‐TEs, we describe the development of a substrate peptide‐based p ‐nitrophenyl phosphonate (PNP) for NRPS‐TEs as a surrogate of DPP and FP (Figures 1C and 2C).…”
Section: Introductionmentioning
confidence: 99%